(untitled) (The Strategic Review for Southern Africa, 2021)
In the West African region, one conflict that has ravaged the nations since 2009 is the Boko Haram Insurgency which is located in Nigeria. This Islamist group is indisputably the most dangerous group confronting Nigeria today with their violent activities ranging from political and socio-economic to security and governance aspects. Boko Haram has managed to wipe out thousands of Nigerians since its inception in 2009, with an attempt to take power from the legitimate government of Nigeria. Boko Haram’s ethnic, religious, and regional fault-lines do not only impact Nigeria but people beyond the borders of Nigeria. A quick review of the current ongoing scholarly debate on the activities of Boko Haram reveals that scholars have not paid much attention to the group’s funding, recruitment, and major attacks in combination for better apprehension when reading. In cases where such has been analysed, it has been individually analysed and most of these studies are five-ten years old. Hence, such information needs an update to remain relevant in cases where they are still poised to be relevant. Therefore, this article’s central objective is to analyse the three identified themes using a decolonial perspective. It argues that Boko Haram’s ongoing campaign of terror is inextricably linked to the funding it continues to receive and strong recruitment tactics